Acute effect of high-intensity functional training (HIFT) using a benchmark on cognition and physiological parameters according to the competitive level - De Brito, M. A.; Fernandes, J. R.; de Carvalho, P. H. B.; Brito, C. J.; Aedo-Munoz, E.; Soto, D. A. S.; Miarka, B. (Journal of Physical Education and Sport, 2023)
Analyze the acute effect of high-intensity functional training on cognition and physiological parameters according to performance. Thirty-two practitioners were divided into groups according to their performance: Elite (n=07; age: 28.9±4.7 years), Advanced (n=10; age: 33.4±4.6 years), and Beginner (n=15; age: 30.6±7.1 years). This research compares the groups and pre-HIFT and post-HIFT moments and correlations for physiological and cognition. Statistical analysis used ANOVA repeated measures and Pearson`s correlation coefficient. Data are mean (M) ± standard deviation (SD). Applied the Five-digit test, evaluated the physiological parameters, and performed the WOD Fran. Showed a significant difference concerning the performance of the HIFT time (E:177.1±29.8s < A: 314.3±46.8s and B: 538.2±102.1s) and difference in cognition regarding the comparison between moments: reading (E:76.4±20.2 > A:75.5±28.9 and B:74.6±22.3 Pk), counting (E: 86.4±10.7 ? A:77.5±20.6 and B:81.1±21.1Pk), choice (E:89.3±9.8 ? A:89.0±9.7 and B:74.6±22.8Pk), shifting (A:91.0±8.4 > E:86.4±10.7 and B:76.4±21.7Pk), inhibition (A:76.5±12.5 > E:76.4±20.2 and B:68.6±18.3Pk), flexibility (A:93.0±6.3 > E:89.3±9.8 and B:86.1±11.1Pk), lactate (E:13.1±1.8 < A:15.1±3.2 and B:16.1±3.7mmol), heart rate (E:188.0±6.6 > A: 174.1±16.1 and B: 185.1±8.9bpm), systolic blood pressure (E:149.7±11.5< A:151.0±9.3 and B:152.5±8.1mmHg), and diastolic blood pressure (E:73.4±6.2 > A:72.8±9.6 and B:69.3±7.1mmHg). Our results confirm that high-intensity exercise improves cognitive functions.